Perception of doctor-patient relationship by external users of a medicine department - Ramos-Rodríguez, Claudia (2008)
Introduction: Physician-patient relationship is the most important power for health recovery. Nevertheless it appears threatened by the many changes affecting today’s medical practice. Objectives: To determine patient’s perception on the quality of the doctor–patient relationship and its association with physician’s and patient’s characteristics. Design: Observational study, inquiry type. Setting: Department of Medicine, Hospital Nacional Daniel Alcides Carrion, Callao, Peru, a teaching hospital. Participants: Medicine outpatient patients. Interventions: A semi-opened questionnaire with 21 questions was applied to systematically selected patients when leaving the doctors’ office. Main outcome measures: Quality of doctor-patient relationship. Results: One hundred and sixty-eight patients were inquired, 39,9% had been previously attended in other place for the same health problem, 51,2% were attended for the first time. An adequate doctor-patient relationship was found in 92,3% and 89,3% were very satisfied. The quality of doctorpatient relationship perceived was strongly associated to medical attention satisfaction (p <0,001, OR 61,2). Both were associated with recommending the doctor (OR 298 and OR 48 respectively). Conclusions: We found an adequate doctor-patient relationship in 92,3%, and 89,3% said they were very satisfied with the medical attention.